New prospects of uranium mineralisation of the Trans-Urals based on regional geochemical survey data - L. A. Krinochkin; O. K. Krinochkina; V. I. Blokov (Известия высших учебных заведений: Геология и разведка, 2022)
Introduction. The article presents the prospects of uranium mineralisation in the Trans-Urals. The study area lies in the southwestern part of the Western Siberian Plate and belongs to the West Siberian uranium-bearing belt. The belt controls the paleovalley type uranium infiltration mineralisation of the Mesozoic age. The data obtained from the anomalous geochemical area (AGA) of the Dolmatovsky and Khokhlovsky uranium ore regions are used as a reference with suitable geochemical characteristics. Aim. The aim of this study is to identify and forecast new uranium ore regions that are promising for the discovery of industrial deposits of paleovalley type uranium.Materials and methods. The research was conducted while establishing the geochemical bases on a scale of 1 : 1 00 000. Over 2000 samples of soils and bottom sediments were evaluated on a 10 × 10 km grid. The uranium active forms and other 56 elements were detected in the samples. The analysis was carried out by inductively coupled plasma mass spectrometry (ICP-MS) in the FSBI “IMGRE” analytical centre.Results. Besides the known Dolmatovsky and Khokhlovsky uranium ore regions, 31 AGAs with uranium specialisation were identified based on the geochemical data obtained in a well-developed and accessible site. Their prospectivity was assessed according to a set of geological and geochemical criteria. As a result, six new promising areas for discovering industrial uranium deposits were identified, and a significant increase in uranium reserves is expected in the well-known Khokhlovsky region.Conclusions. The practical implication of the study is the forecast of the expansion of the uranium raw materials base around the known deposits with finite raw materials reserves.